Preparing Teachers in a Pedagogy of Third Space: A Postcolonial Approach to Contextual and Sustainable Early Childhood Teacher Education. Issue 1 (2nd January 2020) - Gupta, Amita
ABSTRACT: This article draws from a series of qualitative inquiries conducted with early childhood teachers in some Asian countries (primarily India) and interrogates the sustainability of applying Euro-Western pedagogical frameworks to inform the preparation of early childhood teachers who will teach in non-western contexts. The author suggests a more critical, contextual, and culturally appropriate approach to teacher education to ensure that children's well-being is nurtured and their rights are protected by preparing teachers in teacher education classrooms where culturally diverse local and global worldviews on child development and educational philosophies are explored and acknowledged. Framed by the lenses of globalization and postcolonial theory, and drawing on the notion of cultural and pedagogical hybridity, an argument is made for teacher education to be designed as a postcolonial model that will help address the dissonance between theory and practice, and increase educational sustainability.